Consumption taxes, income distribution and poverty: Evidence from Kenya - Beate Jochimsen; Anne Wanyagathi Maina (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2019)
No Poverty' and 'Reduced Inequalities' are two out of the 17 sustainable development goals of the United Nations. Nowadays, Kenya faces high levels of poverty and inequality: 36 percent of the population live below the poverty line and the Gini coefficient was 0.445 in 2015. Against this background, this paper investigates how consumption taxes can be used to reduce poverty and promote income equality in Kenya. Using econometric models we show the effect of consumption taxes on income inequality and on GDP per capita. In line with the literature, our findings confirm that consumption taxes are regressive. Thus, fiscal policy could reduce this consequence by using differentiated tax rates with lower rates applied to basic goods on which the poor spend a higher share of their disposable income. In Kenya, consumption tax revenue is positively related to the GDP per capita. This might point to a successful fiscal policy in Kenia that uses consumption tax revenue to provide essential facilities for the poor leading to an increase of overall welfare. – – Zu den Zielen für eine nachhaltige Entwicklung der Vereinten Nationen zählen sowohl die Beseitigung von Armut als auch das Erlangen von weniger Ungleichheit. Derzeit prägen Armut und Ungleichheit Kenia: 36 Prozent der Bevölkerung leben unter der Armutsgrenze, im Jahr 2015 betrug der Gini Koeffizient 0,445. Vor diesem Hintergrund untersucht diese Arbeit den Einfluss von Konsumbesteuerung auf Einkommensverteilung und Wohlfahrt in Kenia. Mit Hilfe von ökonometrischen Modellen untersuchen wir, inwiefern Konsumbesteuerung zur Reduktion von Ungleichheit, gemessen am Gini-Koeffizient, und zur Wohlfahrtssteigerung, gemessen am Pro-KopfEinkommen, führen kann. Im Einklang mit der Literatur können wir bestätigen, dass Konsumsteuern regressiv wirken. Diese Wirkung kann jedoch durch differenzierte Steuersätze abgeschwächt werden. Das Pro-Kopf-Einkommen in Kenia lässt sich mit Hilfe von Konsumsteuern steigern. Das deutet darauf hin, dass in Kenia das Konsumsteueraufkommen zur Bereitstellung öffentlicher Güter, die überproportional die unteren Einkommensschichten nutzen, verwendet wird und dadurch die Wohlfahrt steigt.
Keywords: H29; O55; O43; I32; 330; consumption taxes; income inequality; poverty; Kenya; Verbrauchssteuer; Einkommensungleichheit; Armut